MICE Management Training: Preparing Taruna Bangsa Private High School Students to Become Professional Event Organizers - Mega Harefa; Lidia Siboro; Jimmy Kelana; Tina Linda (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
This study explores the implementation of a Community Service Program (PKM) focused on MICE (Meetings, Incentives, Conventions, and Exhibitions) management training aimed at preparing students from Taruna Bangsa Private High School to become professional event organizers. The program's objective is to equip students with essential skills and knowledge in event management, which includes planning, coordination, marketing, and logistics, as well as enhancing their soft skills such as communication, leadership, and teamwork. Through a series of workshops, practical sessions, and simulations, students are provided with hands-on experience to understand the intricacies of the event management industry. The training also emphasizes the importance of professionalism, creativity, and problem-solving in organizing successful events. This initiative not only enhances the students' career readiness but also supports the development of the local tourism and event sectors. The program's success is measured by the students' ability to plan and execute mock events, with feedback collected from both the participants and event professionals. The findings highlight the potential of MICE management training in fostering the next generation of skilled professionals and contributing to the growth of Indonesia's event management industry.